The rational thinking of expert opinion and communicating in courtroom - Bing Li; Yuanfeng Wang (Wolters Kluwer Medknow Publications, 2017)
Since the past half century, expert testimony has played an increasingly important role in Chinese litigation. As the amount of expert testimony has grown, the issues about its admissibility and scientific foundation related to evidence are becoming to be questioned commonly. Since eighteenth central committee (China) adopted the decision of the Central Committee of China on several important issues in promoting the legal system, the evidence was redefined to become the predominance in the whole proceeding. This article reviews the expert knowledge implicit in the opinions. It argues that the expert opinions ask judges to be aware of the role of communicationg between participants. Expert opinion is not only gained from laboratory, but also socially constructed in the rational expression and communication, which requir us think logically in terms of legal perceptions of science and expert knowledge in the empirical world.